Effect of microwave sintering temperature on structure and properties of bioceramics based on biogenic hydroxyapatite - Tovstonoh, H.; Sych, O.; Skorokhod, V. (Functional Materials, 2014)
The present work demonstrates the possibility to produce medicine-aimed ceramics on the basis of biogenic hydroxyapatite with structural-mechanical properties required for replacement of the bone tissue defects using techniques of microwave sintering at 800-1100°C. It has been established that porosity of the bioceramics obtained in the temperature range of 800-1000°C (5 min exposure to the maximal temperature) equals about 40 %, whereas at 1100°C it decreases down to 37 %. Compression strength increases with increasing the temperature from 25 to 38 MPa.